2017
DOI: 10.1016/j.micromeso.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Dual-function hydrotalcite-derived adsorbents with sulfur storage properties: Dyes and hydrotalcite fate in adsorption-regeneration cycles

Abstract: Thermal treatment of hydrotalcite at increasing temperatures resulted in formation of mixed oxides that exhibited different adsorption behavior toward anionic and cationic industrial dyes. The material annealed at 450 ○ C was characterized by the highest maximum adsorption capacity for both types of dyes. The adsorption was strongly pH dependent and for the anionic dye abatement low pH was favored whilst higher pH was more preferable for removal of the cationic dye. According to the equilibrium experiments, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For cationic dyes MEB and RhB, the equilibrium time was 100 min, which was faster than that of other materials. 32,33 However, for the anionic dye MO, the equilibrium time was 500 min because additional time was required for MO to enter the pores due to the weak relationship between MO and POP-TCE-15.…”
Section: Resultsmentioning
confidence: 99%
“…For cationic dyes MEB and RhB, the equilibrium time was 100 min, which was faster than that of other materials. 32,33 However, for the anionic dye MO, the equilibrium time was 500 min because additional time was required for MO to enter the pores due to the weak relationship between MO and POP-TCE-15.…”
Section: Resultsmentioning
confidence: 99%
“…Aer a very rapid adsorption, the uptake rates slowly declined with time and reached equilibrium values at approximately 10 min for all the three dyes, which was faster than for some other materials. 38,39 The equilibrium adsorption rates constant(K 2 ) of the MEB, BF, and MG were 0.0026, 0.0149 and 0.0093 g mg À1 min À1 , respectively, those K 2 value were larger than those previously reported porous adsorbents for the three dyes are listed in Table S2. † The high initial uptake rate and the short adsorption equilibrium time demonstrated that the surfaces of the polymer TPP-SO 3 H had a high density of active sites for dyes adsorption.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, Rose Bengal dye can form H-type aggregates in water and polar, protic solvents [53]. Similar effect, with blue shift due to π-π interactions of phenyl groups in MO, was described in confined spaces of anionic clays [54]. On the contrary to MO anions, which were tightly organized perpendicular to the clay layers, AMB and CR anions were tilted or flat lying in the interlayers but still a hypsochromic shift of the absorption maximum was observed.…”
Section: Uv-vis-drsmentioning
confidence: 76%